2012
DOI: 10.1111/j.1365-3156.2012.03047.x
|View full text |Cite
|
Sign up to set email alerts
|

Practicing medicine without borders: tele‐consultations and tele‐mentoring for improving paediatric care in a conflict setting in Somalia?

Abstract: Abstractobjectives In a district hospital in conflict-torn Somalia, we assessed (i) the impact of introducing telemedicine on the quality of paediatric care, and (ii) the added value as perceived by local clinicians.methods A 'real-time' audio-visual exchange of information on paediatric cases (Audiosoft Technologies, Quebec, Canada) took place between clinicians in Somalia and a paediatrician in Nairobi. The study involved a retrospective analysis of programme data, and a perception study among the local clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…34,35 Beyond this, activity can be seen in many developing countries; for example, Brazil, Cambodia, Ecuador, India, Nepal, Philippines, and South Africa, among others. 32 In Asia, recent growth in application of telehealth has been seen in both India and People's Republic of China, with continued growth expected in the coming decade.…”
Section: Current Usementioning
confidence: 99%
“…34,35 Beyond this, activity can be seen in many developing countries; for example, Brazil, Cambodia, Ecuador, India, Nepal, Philippines, and South Africa, among others. 32 In Asia, recent growth in application of telehealth has been seen in both India and People's Republic of China, with continued growth expected in the coming decade.…”
Section: Current Usementioning
confidence: 99%
“…Other studies have demonstrated the effectiveness of similar programs for other medical specialties [10,11]. In the future, the development of a civilian medical toxicology teleconsultation service to assist both local and volunteer physicians in locations with limited subspecialty care may aid in reaching those in greatest need.…”
Section: Discussionmentioning
confidence: 99%
“…Médecins Sans Frontières has previously used both store-and-forward and real-time telemedicine (5, 6). Although the real-time telemedicine work was considered successful, the requirement for good quality Internet connections makes real-time telemedicine much more expensive than store-and-forward work.…”
Section: Discussionmentioning
confidence: 99%